2021
DOI: 10.3389/fnano.2021.644564
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery With Carbon-Based Nanomaterials as Versatile Nanocarriers: Progress and Prospects

Abstract: With growing interest, a large number of researches have been conducted on carbon-based nanomaterials (CBNs). However, their uses are limited due to comprehensive potential environmental and human health effects. It is often confusing for researchers to make an informed choice regarding the versatile carbon-based nanocarrier system and its potential applications. This review has highlighted emerging applications and cutting-edge progress of CBNs in drug delivery. Some critical factors like enzymatic degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 185 publications
(180 reference statements)
1
55
0
2
Order By: Relevance
“…Carbon-based nanomaterials (CBNs) have attracted a great deal of attention in TDD research because of their unique structural dimensions and physicochemical features [193]. Strasinger et al [194] reported the use of various electrical biases to test the transdermal delivery of clonidine mediated by a carbon nanotube-epoxy nanocomposite membrane.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Carbon-based nanomaterials (CBNs) have attracted a great deal of attention in TDD research because of their unique structural dimensions and physicochemical features [193]. Strasinger et al [194] reported the use of various electrical biases to test the transdermal delivery of clonidine mediated by a carbon nanotube-epoxy nanocomposite membrane.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…They can vary in length, diameter, layer count, and chirality. They possess appealing features due to their unusual blend of strength, stiffness, and elasticity [63]. Due to their outstanding physical and chemical qualities, such as an enormous surface-area-to-volume ratio, hollow structure, small diameter, electrical capabilities, and exceptional optical and high tensile strength, CNTs are used in a wide range of applications.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…These nanomaterials have been employed for the targeted delivery of drugs or for cancer diagnosis. However, there is still concern about their toxicity for both humans and the environment [ 14 ], so most of their cancer-related applications are limited to their use in the development of sensors for cancer biomarkers. Their high surface area and excellent electrical conductivity [ 15 ] make them suitable candidates for the development of the electrochemical sensors used for the detection of biomarkers that are expressed in HCC [ 16 , 17 , 18 ].…”
Section: Types Of Nanoparticles Used For Diagnosis and Treatmentmentioning
confidence: 99%